A multiple warning and smart monitoring system using wearable devices for home care. Issue 136 (April 2020) - Hung, Lun-Ping; Lin, Chun-Cheng
Highlights: A smart system for assistance in remote home self-care process is proposed. It conducts real-time patient information (e.g., psychological status) analysis. Electrocardiogram home monitoring is applied for those after cardiovascular surgery. By a private cloud, professional medical advices and response measures are supported. Experiments shows reduction of personnel costs and promotion of medical service. Abstract: In line with the advanced medical technologies and popularity of media (especially, social media), an emerging trend regarding remote home care services has received increasing attention. This paper proposed a smart system for assistance in the home self-care process, which concentrates on a management process for real-time analysis on patient information (e.g., psychological status). The proposed system provides the EKG (electrocardiogram) home monitoring function for the care of patient cases after cardiovascular surgery. To provide supports for self-care at home, a private cloud was employed to design intelligent modules that implemented the smart system. In addition, professional medical advices and response measures were proposed so that individuals could safely and effectively engage self-care at home under the support. We conducted a user study, and the experiment results showed that the proposed approach can reduce partial costs on human resources for home care and enhance the quality of medical service, thereby achieving the goal of seamless integration of external healthcare systems of hospital.